Managing and resisting 'degeneration' in employee-owned businesses: A comparative study of two large retailers in Spain and the United Kingdom. (September 2014) - Storey, John; Basterretxea, Imanol; Salaman, Graeme
Employee-owned businesses have recently enjoyed a resurgence of interest as possible 'alternatives' to the somewhat tarnished image of conventional investor-owned capitalist firms. Within the context of global economic crisis, such alternatives seem newly attractive. This is somewhat ironic because, for more than a century, academic literature on employee-owned businesses has been dominated by the 'degeneration thesis'. This suggested that these businesses tend towards failure—they either fail commercially, or they relinquish their democratic characters. Bucking this trend and offering a beacon—especially in the United Kingdom —has been the commercially successful, co-owned enterprise of the John Lewis Partnership whose virtues have seemingly been rewarded with favourable and sustainable outcomes. This article makes comparisons between John Lewis Partnership and its Spanish equivalent Eroski—the supermarket group which is part of the Mondragon cooperatives. The contribution of this article is to examine in a comparative way how the managers in John Lewis Partnership and Eroski have constructed and accomplished their alternative scenarios. Using longitudinal data and detailed interviews with senior managers in both enterprises, it explores the ways in which two large, employee-owned, enterprises reconcile apparently conflicting principles and objectives. The article thus puts some new flesh on the 'regeneration thesis'.